Complete Genome Sequence of Two Variant Porcine Reproductive and Respiratory Syndrome Viruses Isolated from Vaccinated Piglets - Zhang, Guanqun (American Society for Microbiology, 2012)
Porcine reproductive and respiratory syndrome virus (PRRSV) continues to affect the Chinese swine industry. Since 2006, variant PRRSV strains sharing two unique discontinuous deletions of 30 amino acids in the nonstructural protein Nsp2 have become dominant in Chinese swine herds and have caused huge economic losses to the swine industry in China. Here we report the complete genome sequence of two novel PRRSV variants isolated from vaccinated piglets with additional amino acid deletions in Nsp2.